Answers offered by computer algebra systems to equations from school textbooks - Tonisson, Eno; Velikanova, Nadezhda (Teaching Mathematics and Computer Science, 2008)
This paper is an attempt to develop a strategy and methods for investigating and comparing the answers offered by computer algebra systems and the school answers. After primary (pilot) investigation of how well 8 computer algebra systems handle equations from school textbooks, it is possible to conclude that the systems are mostly reliable and give reasonable answers. Some remarks regarding a somewhat unexpected answer obtained can be easily explained by built-in standards and notions, which can differ from school assumptions. In other cases the differences from school could be corrected by certain commands.